SUICIDAL INJURIES FROM HEIGHT FALLS - Pavlovski, Goran; Stankov, Aleksandar; Jakjovski, Zlatko; Bitoljanu, Natasha; Belakaposka Srpanova, Viktorija; Cakar, Ljupco; Ivcheva, Ana; Poposka, Verica (Journal of Morphological Sciences, 2022)
According to the manner of death, falls from height can be accidental, homicidal and predominantly suicidal. The type of injuries in suicidal falls from height depend to a large extent on the height of the fall, the part of the body that landed and suffered the first impact, the age and the body weight of the victim, clothes worn and body composition. Although with prospect, the research is an average study of the Institute for Forensic Medicine in Skopje, conducted on 80 victims of fatal falls from different heights, through forensic-medical autopsy. The data for all examined cases have been taken from the forensic-medical autopsy reports. The study analyses the cases which appear to be suicides, according to the manner of death. The injuries inflicted from the falls are analysed according to the height in three groups: small height up to 7 meters, middle height from 7 to 10 meters and big heights above 20 meters. Study results have shown that 25% of the analysed cases are suicides. The analysis of the number and severity of the injuries in relation to the height of the fall prove that the fractures of the hipbone and legs were most frequent injuries found in the victims who have fallen from 7 to 20 meters. In the victims of height falls up to 7 meters, most frequent injuries were the fractures of the ribs and the spine. In falls from height above 20 meters, all organs were equally damaged. In suicides from falls from height, most frequent injuries of the skeleton were fractures of the ribs and spine, while the liver was the most affected organ among the internal organs. However, the type of injuries determined with the autopsy is not a sufficient indicator for successful assessment of the manner of death in fatal falls from height. Key words : fall from height, type of injury, suicide.